KESADARAN EKOLOGIS DALAM IMAN KRISTEN: TANGGUNG JAWAB ETIS TERHADAP LINGKUNGAN HIDUP - Dusen Beis; Oktaviana Manno Bire (Adisam Publisher, 2026)
Environmental degradation has become a pressing global challenge that calls for ethical responses from all sectors of society, including the Christian faith community. This article aims to examine ecological awareness within the Christian faith and the ethical responsibility of believers toward the environment. This study employs a qualitative research method with a literature review approach, drawing on biblical texts, theological sources, and scholarly discussions on ecotheology and Christian ethics. The findings indicate that the Christian faith fundamentally teaches human responsibility as God’s creation to care for and preserve the natural world. The concept of stewardship emphasizes that excessive exploitation of nature contradicts God’s will. Therefore, ecological awareness is not merely a social or environmental concern but an integral part of Christian faith and practice. This article affirms that churches and believers have a strategic role in fostering ethical attitudes, ecological spirituality, and concrete actions to protect environmental sustainability as an expression of obedience to God.